Development of international competitiveness and foreign economic activity of enterprises (International relations and international law Journal, 2017)
The competitiveness of the enterprise – is the real potential and the ability of companies, as well as availability for to them to have opportunity to design, produce and market products that are on the price non-price characteristics of the complex more attractive to the consumer than competitor products. The possibility of the country takes its rightful place in the global economy and depends on the ability of its companies to retain worthy place on the world markets. Therefore, in the modern world, achieving and maintaining competitiveness on foreign markets is a necessary condition to enhance national competitiveness. It is necessary to take into account the trends of global development and in accordance with them to pursue policies aimed not only at reducing the cost of production and sales of products, but also at the need to comprehensively improve the effectiveness and the internal and external factors for the competitiveness of the company.
Keywords: competitiveness; international competitiveness; competitive advantage